Running ragged : the impact of school-to-family spillover on familial relations among female and male undergraduates during the COVID-19 pandemic and the protective effect of family resilience - Tok, Clarin Qian Le (Nanyang Technological University, 2022)
Stress can emanate in a wide range of manifestations and originate from different spheres of life. Stress derived from academic settings, in particular, has garnered a considerable amount of research attention. Past studies have circumscribed undergraduates as a distinct group that has been experiencing unprecedented levels of stress, compared to the general population. According to extant spillover theories, the elevated stress levels of students can spillover to other aspects of life, such as familial relations, and give rise to familial dispute. Male and female undergraduates may also experience different amounts of spillover. Hence, the present study aimed to examine the impact of school spillover on family relationship quality as well as the moderating role of gender. In light of the current pandemic climate, the moderating effects of COVID-19 stress and family resilience were explored as well. Eighty-eight undergraduates, aged between 21 to 27 years, were recruited to complete a survey covering perceived academic stress, school-to-family spillover, family relationship quality, COVID-19 stress, and family resilience. The results indicated: (1) significant positive associations between perceived academic stress and school spillover, (2) significant positive effect of school spillover on family relationship quality, and (3) significant moderation of family resilience. Moderation effect of gender and effect of COVID-19 stress was not found. Implications and limitations of these findings were discussed. Keywords: academic stress, school-to-family stress spillover, family relationship quality, COVID-19 stress, family resilience